Medial temporal pathways for contextual learning: Network c-fos mapping in rats with or without perirhinal cortex lesions. (10th March 2017) - Kinnavane, Lisa; Amin, Eman; Olarte-Sánchez, Cristian M.; Aggleton, John P.
Background: In the rat brain, context information is thought to engage network interactions between the postrhinal cortex, medial entorhinal cortex, and the hippocampus. In contrast, object information is thought to be more reliant on perirhinal cortex and lateral entorhinal cortex interactions with the hippocampus. Method: The 'context network' was explored by mapping expression of the immediate-early gene, c- fos, after exposure to a new spatial environment. Results: Structural equation modelling of Fos counts produced networks of good fit that closely matched prior predictions based on anatomically grounded functional models. These same models did not, however, fit the Fos data from home-cage controls nor did they fit the corresponding data from a previous study exploring object recognition. These additional analyses highlight the specificity of the context network. The home-cage controls, meanwhile, showed raised levels of inter-area Fos correlations between the many sites examined, that is, their changes in Fos levels lacked anatomical specificity. A total of two additional groups of rats received perirhinal cortex lesions. While the loss of perirhinal cortex reduced lateral entorhinal c- fos expression, it did not affect mean levels of hippocampal c- fos expression. Similarly, overall c- fos expression in the prelimbic cortex, retrosplenial cortex, and nucleus reuniens of the thalamus appeared unaffected by the perirhinal cortex lesions. Conclusion: The perirhinal cortex lesions disrupted network interactions involving the medial entorhinal cortex and the hippocampus, highlighting ways in which perirhinal cortex might affect specific aspects of context learning.